Genome-wide identification of GH17 family genes and their expression patterns associated with bud dormancy-regrowth regulation in Prunus persica - Zhao, Xuehui; Xie, Haifeng; Han, Yifei; Zhang, Jiaqi; Qi, Yihua; Zhang, Zejie; Sun, Maoxiang; Liu, Meiying; Wang, Fen; Wang, Qingjie (Frontiers in Plant Science, 2025)
Introductionβ-1,3-glucanase (GH17), which is necessary for symplastic transport during dormancy establishment, maintenance, and release, plays important roles in regulating cell-cell communication through plasmodesmata. However, the comprehensive identification of GH17s in peach and their function in bud dormancy regulation is still poorly understood. MethodsForty-eight PpGH17 genes were identified from the peach genome and analyzed for phylogenetic relationships, conserved motifs, gene structure, domains, chromosomal location, syntenic relationships and cis-acting elements. Gene expression patterns were validated using qRT-PCR and protein interactions were confirmed by Y2H assays and BiFC assays.ResultsThese 48 PpGH17 members in peach were classified into three major clades, namely, α, β, and γ, and were distributed unevenly across eight chromosomes. Cis-element analysis of the PpGH17 genes revealed that a large number of PpGH17 family members could respond to ABA or GA. By re-analyzing a RNA-seq data, ten PpGH17 genes in peach and apricot showed significantly changed expression during the transition from endodormancy to ecodormancy. The expression patterns of the PpGH17 genes during different dormancy stages in peach showed that these genes were closely associated with dormancy release and bud regrowth regulation. The GCC box-like element was found in the promoter sequence of eleven PpGH17 genes, suggesting that they may be directly regulated by PpEBB1 and may participate in the bud-break stage. Y2H assays and BiFC assays showed PpGH17-8 can interact with PpKINβ2 and PpMIEL1. DiscussionOur study provides a foundation for understanding the functions of PpGH17 genes in regulating peach bud dormancy. Furthermore, this study will facilitate the identification of key candidate genes for molecular breeding and genetic engineering efforts targeting dormancy-related traits in peach.